The efficacy of acyclovir in treatment of the pemphigus vulgaris - Fariba Iraji; Gita Faghihi; Amir Hossein Siadat (Journal of Research in Medical Sciences, 2013)
Background: Pemphigus is a group of autoimmune blistering diseases of the skin and mucous membranes caused by the presence of antibodies against adhesion molecules on the cell surface of keratinocytes. The possible role of herpes simplex virus infection in the pathogenesis of pemphigus vulgaris (PV) has been suggested. In this study, we evaluated the impact of a course of acyclovir in improvement of the pemphigus patients and reduction of the hospitalization duration. Materials and Methods: A total of 30 patients with definitive diagnosis of PV were recruited in study. They were randomized in two groups. One group received routine treatment and another received the routine plus 2 week course of oral acyclovir (1200 mg/day). The improvement was defined as a more than 50% change in baseline severity score of the disease. All data was registered at the checklists and after follow-up period, the statistical analyses were performed by aid of t-test and Fisher′s exact test. Results: There was no statistically significant difference in mean severity score and improvement rates between two groups at the end of study (P > 0.05). Meanwhile, there was no statistical difference in duration of hospitalization in two groups (P > 0.05) though the severity score and hospitalization duration were apparently less in acyclovir-group than control group. Neither of the patients (in acyclovir group) showed any side effect. Conclusion: We did not observe any difference between response to treatment and hospitalization period in the group that was treated with acyclovir as compared with control group. However, the partial and complete remissions were higher in patients on acyclovir therapy compared to controls. In those pemphigus patients who do not respond to sufficient immunosuppressive regimen or show a sudden relapse after reaching partial or complete clinical remission, a trial of oral acyclovir therapy may have promising result.